Safety and immunogenicity of BNT162b2 mRNA COVID-19 vaccine in adolescents with rheumatic diseases treated with immunomodulatory medications. (18th February 2022) - Heshin-Bekenstein, Merav; Ziv, Amit; Toplak, Natasa; Hagin, David; Kadishevich, Danielle; Butbul, Yonatan A; Saiag, Esther; Kaufman, Alla; Shefer, Gabi; Sharon, Orli; Pel, Sara; Elkayam, Ori; et al.
Abstract: Objectives: Adolescents with juvenile-onset autoimmune inflammatory rheumatic diseases (AIIRDs) could be at risk for disease flare secondary to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or to withholding anti-inflammatory therapy. While vaccination can protect against coronavirus disease 2019 (COVID-19), safety and immunogenicity data regarding anti-SARS-CoV-2 vaccines among adolescents with AIIRDs are limited. This international, prospective, multicentre study evaluated the safety and immunogenicity of the BNT162b2 anti-SARS-CoV-2 vaccine among adolescents and young adults with juvenile-onset AIIRDs, 80% of whom are on chronic immunomodulatory therapy. Methods: Vaccine side effects, disease activity and short-term efficacy were evaluated after 3 months in 91 patients. Anti-spike S1/S2 IgG antibody levels were evaluated in 37 patients and 22 controls 2–9 weeks after the second dose. Results: A total of 91 patients and 40 healthy controls were included. The safety profile was good, with 96.7% ( n  = 88) of patients reporting mild or no side effects and no change in disease activity. However, three patients had transient acute symptoms: two following the first vaccination (renal failure and pulmonary haemorrhage) and one following the second dose (mild lupus flare vs viral infection). The seropositivity rate was 97.3% in the AIIRD group compared with 100% among controls. However, anti-S1/S2 antibody titres were significantly lower in the AIIRD group compared with controls [242 (s .d . 136.4) vs 387.8 (57.3) BAU/ml, respectively; P  < 0.0001]. No cases of COVID-19 were documented during the 3 month follow-up. Conclusion: Vaccination of juvenile-onset AIIRD patients demonstrated good short-term safety and efficacy and a high seropositivity rate but lower anti-S1/S2 antibody titres compared with healthy controls. These results should encourage vaccination of adolescents with juvenile-onset AIIRDs, even while on immunomodulation.